“Both Man and Woman”: The Third Sex/Gender Role in Roma Community in Skopje - Ines Crvenkovska Risteska (Etnoantropološki Problemi, 2019)
“Women” (buljàshi) play a third gender role in the Roma community in Skopje, Macedonia. Their important role, “both man and woman”, in the Roma community is realized through economic, social, and ritual community of close “sisters”. Within the Roma family rituals, in the life cycle rituals of the men and women community members, they take a significant ritual - magic function. They are “mediators” between the divine and the community.